The metaphoric effect of metaphor/metonymy in Michel Pêcheux - Cattelan, João Carlos (2021)
In this study, by collating mainly Michel Pêcheux’s works, Metaphor and Interdiscourse ([1984] 2011) and Observations for a General Theory of Ideologies ([1967] 1995), I aim to verify how the concepts of metaphor and metonymy are conceived by the French author; examine how the interrelation established between them is thought; thematize the overlap, on the one hand, between metaphor, semantics and empirical ideology and, on the other, between metonymy, syntax and speculative ideology; address these issues with examples that serve as data; and estimate how they, based on the conception of language either as a system of signs or as a means of communication, respectively, restrain, in one case, the genesis of the symbolic order and, in another case, the effect of society on the effect of language.